PENGARUH DISIPLIN DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI PADA DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KABUPATEN OGAN KOMERING ULU - Riki Adriant; Desky Pernando (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
This study discussed the influence of discipline and teamwork on employees’ performance at the fire and rescue service in Ogan Komering Ulu Regency. The population in this study were 44 respondents, the data collection technique used in this study was through the distribution of questionnaires. The analytical method used was a quantitative method using multiple linear regression analysis tools. The results of the analysis in this study explained the t count of each discipline variable (X1) of 6.765 and teamwork (X2) of 2.385 which was greater than the t-table value of 2.019 which stated that each variable had a partial influence on the employees’ performance of fire and rescue service of ogan komering ulu regency. Simultaneously there was the influence of discipline and teamwork on the performance of the fire and rescue service employees in Ogan Komering Ulu Regency with Fcount of 371.192 which was greater than Ftable of 3.23. The coefficient of determination (R square) of 0.948 means that in this case the contribution of discipline and teamwork was 94.8%, while the remaining 5.2% was influenced by other variables not examined in this study such as work motivation and work culture.